2009
DOI: 10.1093/ndt/gfp132
|View full text |Cite
|
Sign up to set email alerts
|

Therapy outcome in peritoneal dialysis patients transferred from haemodialysis

Abstract: Our data suggest that outcome of patients transferred from HD is similar to that achieved in patients in whom PD is the first choice therapy. Thus, this option should be strongly considered in patients experiencing complications on HD, mainly vascular access problems, heart failure or intradialytic hypotension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 16 publications
5
27
0
Order By: Relevance
“…3 PDI Our study also suggests that technique survival in transfer and no-transfer patients was similar. That finding is consistent with a previously reported study (6); however, other investigations revealed that technique survival was lower in transferred patients (18,19). Whether a history of HD therapy can or cannot influence peritoneal membrane function is still beyond our knowledge, but some evidence still indirectly favors our results to some extent.…”
Section: Discussionsupporting
confidence: 94%
“…3 PDI Our study also suggests that technique survival in transfer and no-transfer patients was similar. That finding is consistent with a previously reported study (6); however, other investigations revealed that technique survival was lower in transferred patients (18,19). Whether a history of HD therapy can or cannot influence peritoneal membrane function is still beyond our knowledge, but some evidence still indirectly favors our results to some extent.…”
Section: Discussionsupporting
confidence: 94%
“…These causes may be biologic or a result of unmeasured and/or unaccounted bias. Often, a switch from PD to HD relates to the technique failure, whereas problems with vascular access, higher risk of cardiovascular disease, or personal preference are commonly cited when HD patients switch to PD (21,22). In our study, patients with the same transplantation status had similar characteristics regardless of whether they changed an initial modality (Table 1).…”
Section: Discussionmentioning
confidence: 75%
“…21 PD requires a significant patient compliance, family support, and a clear understanding about the application technique. As the first choice of treatment modality, PD should be applied treatment under suitable conditions.…”
Section: Discussionmentioning
confidence: 99%